Anxiety sensitivity in Croatian War Veterans: Pilot Study - Jokić-Begić, Nataša (Array, 2007)
Anxiety sensitivity is the fear of anxiety symptoms, arising from beliefs that these symptoms and associated physical sensations may have negative physical, psychological and social consequences. There is growing evidence that anxiety sensitivity plays important role in PTSD. The aim of this study was to compare severity of anxiety sensitivity, trait and state anxiety and depression among PTSD patients, patients with other anxiety disorders and normal controls. This is first research of anxiety sensitivity among Croatian war veterans. The study involved three groups: war veterans with PTSD (n=50), other anxiety disorders group (apart from panic disorder) (n=50), and normal controls (n=50). All participants were male. Anxiety Sensitivity Index (ASI), Beck depression inventory (BDI) and State-Trait Anxiety Inventory (STAI) were administered. In all administered scales clinical samples (PTSD group and group with other anxiety disorders) scored significantly higher then normal controls. PTSD patients reported highest levels of anxiety sensitivity, state and trait anxiety and depression. High positive correlations were identified between measured variables for PTSD group and normal controls. At the same time, group with other anxiety disorders showed significant but low correlations.